Odpowiedzi

2010-04-15T14:59:55+02:00
2c-5=3
2c=3+5
2c=8
c=4


3(y+2)=9
3y+6=9
3y=9-6
3y=3
y=1


2a-(4a-1)=4
2a-4a+1=4
-2a=4-1
-2a=3
a=-1,5


y-4=10
y=10+4
y=14


3+x=5
x=5-3
x=2


9-b=4
-b=4-9
-b=-5
b=5
  • Użytkownik Zadane
2010-04-15T15:00:49+02:00
2c-5=3
2c=3+5
2c=8
c=4


3(y+2)=9

3y+6=9
3y=9-6
3y=3
y=3


2a-(4a-1)=4
2a-4a+1=4
2a-4a=4-1
-2a=3
a=-3/2



y-4=10

y=10+4
y=14

3+x=5
x=5+3
x=8

9-b=4
- b=4-9
-b=-5
b=5


milego dnia:)
2010-04-15T15:01:09+02:00
2c-5=3
2c=3+5
2c=8/:2
c=4

3(y+2)=9
3y+6=9
3y=9-6
3y=3/:3
y=1


2a-(4a-1)=4
2a-4a+1=4
2a-4a=4-1
-2a=3
a=-1.5

y-4=10
y=10+4
y=14

3+x=5
x=5-3
x=2

9-b=4
9-4=b
5=b
b=5